Towards a Prototyping Approach in Systems Development - Mogensen, Preben Holst (DAIMI Report Series, 1992)
This paper explores the notion of ’provocation through concrete experience’ towards a provotyping approach. It addresses the question: How do we on the one hand, devise qualitatively new systems, and on the other hand, ensure their usability in a given practice? The notion of provocation through concrete experience is developed through an investigation of prototyping and activity theory. Exploration of this notion leads to the idea of the system developer ’provoking’ concrete, everyday practice, by exposing current problems, calling forth what usually is taken for granted. Problems with current practice and a lack of mutual understanding, usually conceived of as hindrances to successful systems development, are used constructively. These ideas are compared to four related approaches: Euture Workshops, Metaphorical Design, Cooperative Prototyping, and Or ganizational Games. The comparison serves the twofold purpose of contextualizing the new ideas as well as developing techniques for carrying them out.